HUKUM SEBAGAI ALAT KONTROL SOSIAL: (Suatu Kajian Dalam Perspektif Sosiologi Hukum) - Kandunmas, Fransiskus; Fatlolon, Costantinus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
Laws are created and develops with humans, so that law is a product of ideas, thought patterns, views of life, beliefs and habits which are used as a normative standard which contains provisions and prohibitions to regulate and organize human life in order to create in society. In primordial forms of human life, law has been used even though it is still verbal, and limited in is application. When humans enter to the state life, law is used as a state tool/instrument to guarantee wider public order. Law is a means of control or social control that has supremacy so that it must be obeyed by all in society. Problems often arise when law is no longer an instrument of the state to create collective order, but it’s used by a group of people (oligarchy) as a political vehicle to protect their personal or group interests. Kata kunci: Hukum, Masyarakat, Kontrol Sosial, Ketertiban Umum